Startup Business Types and Their Leaders - Fischer, Mary; Orr, Leah (American Journal of Management, 2023)
In the past few decades, the number of businesses with a market value of one billion USD or more has significantly grown. Aided by new technology and business models, these businesses are a major part of our lives. This discussion explores various startup business types such as unicorns that evolve into billion -dollar ventures, high growth gazelle business that increase their revenue at least 20 percent annually, and dragons that not only have high growth but attain dominance in their industry. The technology employed by these startups in their growth process together with their management and business organizations are presented. A discussion of selected unicorns together with their innovative technology and entrepreneur leadership help to explain the fast-growing startup’s success.